Assessment ofGender Determination: By Morphometric Dimensions ofthe Maxillary Sinuses and Computed Tomography - Dilip Shah; Pradeep Shankarrao Patil; Prithviraj L. Jadhav; Rajat Agnihotri; Neelaja Patil (Asian Journal of Medical Radiological Research, 2019)
Background: Gender determination is considered to be an important step inidentification.For gender determination, anthropometric assessment is one of the main forensic assessments.Objective: The aim of this study was to investigate whether the morphometric dimensions of the maxillary sinuses can be used for gender determination.Subjects and Methods: A total of 147 patients from the age group of 20-70 were included in the study.Out of which 85(57.8%) were males and 62(42.2%) were females, and who came for head and paranasalsinusComputed Tomography (CT) scan in the duration of one year from June 2018 to April 2019 and who had complaints of head ache and suspected sinus diseases but without any pathological radiographic findings or history of trauma and in whom the CT Scans were considered normal as per the consultant radiologists.To obtain the Multiple detector computed tomography (MDCT)images, an MDCT Siemens Somatom Definition AS 64 SLICE machine with a high-resolution bone algorithm, 233 mm field of view, 120 kV, 395 mA, scanning time of 6.5 seconds and slice thickness of 1.0 mm was used to obtain the axial images.Results:The proportion of correctly identified females with right and left sinus was 74.2 % and 77.4% while using right and left sinus 76.5% and78.8% of males were correctly identified respectively. The combined proportion of correctly identified gender was 75.5% using the right sinus and 78.2% using the left sinus.Conclusion: All the parameters were equally and statistically significant in gender determination in our study making imaging of maxillary sinus on CT scan as an important anatomical structure as an aid in forensic anthropology for criminal investigations. Based on the multiple regression analysis a formula is also derived to easily and conveniently calculate the gender based on the values of maxillary sinus obtained on CT scan.